Ideas of Justice and Conflict: Differences between Regulations and Commitments of Coexistence and Youth Perception of Justice in Schools - Nuñez, Pedro (Education Policy Analysis Archives, 2015)
Educational research in the country and the region has a long-standing tradition, since the 80s, in the study of the incidence of the educational processes in the production and reproduction of social and educational inequalities. This article seeks to problematize these issues, by studying a new oriented approach the topics of citizenship and the feelings of injustice by incorporating to the analysis the voice, perceptions and practices of the young people in secondary school. The paper is organized into three sections. At first we present the main features of of the Argentine secondary level and described the regulatory reforms proposed in relation to school life. In a second instance, we analized the guidelines governing coexistence agreements in four secondary schools of the Province of Buenos Aires, Argentina that are located in areas with different characteristics and whose proposal and institutional history sharply differs. Finally, in the third section, we study the feelings of the young people at different conflicts in the school environment. We search into its definition of when a solution is considered “fair” and what represents “un fair”. Following the points made by other studies, we seek to describe which of the inequalities that produces and reproduces the school are considered as such by the students and present the different coexisting visions in the educational system on dissimilar concepts such as coexistence, rights, and justice.